Design of Cost-Effective and Emission-Aware Power Plant System for Integrated Electric Propulsion Ships - Chalermkiat Nuchturee; Tie Li; Hongpu Xia (Journal of Marine Science and Engineering, 2021)
Extensive electrification of ship power systems appears to be a promising measure to meet stringent environmental requirements. The concept is to enable ship power management to allocate loads in response to load variations in an optimal manner. From a broader design perspective, the reliability of machinery operation is also of importance, especially with regard to the failure cost from power outages. In this paper, an approach for determining optimal power plants based on economic and environmental perspectives across several architecture choices is proposed. The design procedure involves the implementation of metaheuristic optimization to minimize fuel consumption and emissions released, while maintenance and repair services can be extracted using reliability assessment tools. The simulation results demonstrated that ship power management using the whale optimization algorithm (WOA) was able to reduce fuel consumption and corresponding emissions in a range from 4.04–8.86%, varying with the profiles, by eliminating inefficient working generators and distributing loads for the rest to the nearest possible energy-saving areas. There was also a trade-off between maintenance service and overall system expenses. Finally, a compromise solution was sought with the proposed holistic design for contradictory cost components by taking into account fuel operation consumption, shore electricity supply, maintenance service and investment expenditure.